Cost-effectiveness analysis of sequential two-step screening versus direct colonoscopy screening for colorectal cancer: a large-scale survey in Eastern China - Fu, Yun; Li, Hao; Xu, Ao; Yang, Zhongrong; Zhang, Peng; Wang, Weibing (Frontiers in Oncology, 2025)
ObjectivesDespite the implementation of colorectal cancer (CRC) screening programs in many regions worldwide over the past few decades, the cost-effectiveness of these programs has been questioned owing to their acceptance rates. In this study, we evaluated the cost-effectiveness of screening strategies, quantified the impact of colonoscopy acceptance rates, and analyzed the underlying factors driving individual preferences.MethodsThe cost-effectiveness of three strategies—no screening, sequential two-step screening (fecal immunochemical test and risk assessment, followed by colonoscopy), and colonoscopy screening—was evaluated from a societal perspective. This assessment was conducted using a decision-tree Markov model with the incremental cost-effectiveness ratio as the primary evaluation criterion.ResultsSequential screening was more cost-effective than colonoscopy screening (19,335 vs. 27,379 United States dollars per quality-adjusted life year). Ideal sequential screening could prevent 32.2%(691/2147) CRC deaths, whereas colonoscopy screening at the same colonoscopy acceptance rate (20.3%) could prevent 17.6%(377/2147) CRC deaths. When the acceptance rate of direct colonoscopy surpasses the threshold of 37.2%, the resulting health benefits likely outweigh those achieved using a the sequential two-step screening approach.ConclusionsSequential screening is recommended for individuals in areas with constrained screening resources or during the early stages of regional screening program implementation. However, once screening habits are established, transitioning to direct colonoscopy screening becomes more favorable. Notably, reducing colonoscopy costs is the principal factor for enhancing an individual’s willingness to undergo the procedure.